2008
DOI: 10.1002/ijc.23909
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐retina antigens as potential paraneoplastic antigens in melanoma‐associated retinopathy

Abstract: Melanoma-associated retinopathy is a rare paraneoplastic neurological syndrome characterized by retinopathy in melanoma patients. The main photoreceptor proteins have been found to be expressed as cancer-retina antigens in melanoma. Here we present evidence that these can function as paraneoplastic antigens in melanoma-associated retinopathy. Sera and one tumor cell line of such patients were studied and ret-transgenic mice spontaneously developing melanoma were used as a murine model for melanoma-associated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Among these, PDE6 is expressed at a high frequency. Such expression of cancer-retina antigens could generate an autoimmune response [8], which in turn might lead to development of a paraneoplastic neurological syndrome, melanoma-associated retinopathy [9]. Furthermore, we demonstrated that expression of cancer-retina antigens can be modulated by light as it proceeds in photoreceptor cells [10].…”
Section: Introductionmentioning
confidence: 87%
“…Among these, PDE6 is expressed at a high frequency. Such expression of cancer-retina antigens could generate an autoimmune response [8], which in turn might lead to development of a paraneoplastic neurological syndrome, melanoma-associated retinopathy [9]. Furthermore, we demonstrated that expression of cancer-retina antigens can be modulated by light as it proceeds in photoreceptor cells [10].…”
Section: Introductionmentioning
confidence: 87%
“…For example, antibodies against a 35-kDa Muller cell protein, 76 a 22-kDa neuronal antigen found in both the retina and optic nerve, 129 and a novel membrane-associated 33-kDa protein 205 have all been described in MAR. Because visual phototransduction proteins are known to be produced by melanoma cells, it should come as no surprise that autoantibodies against transducin-a, 2 transducin-b, 225 arrestin, 27 and rhodopsin 98 are found in MAR patients. The wide diversity of retinal antigens encountered is likely indicative of the immunologic heterogeneity of this disorder.…”
Section: Pathogenesismentioning
confidence: 97%
“…Some patients with MAR have been found to express a variety of autoantibodies against various proteins including transducin-β [11], rhodopsin [47], arrestin [48], a 35-kDa protein in Müller glial cells, a 22-kDa neuronal antigen, mitofilin, titin and COX [49]. Mitofilin is a mitochondrial protein anchored in the inner mitochondrial membrane, presumed to influence the morphological structure and function of mitochondria [49].…”
Section: Antigens and Antibodiesmentioning
confidence: 99%